(untitled) (Journal of the College of Basic Education, 2022)
Epistemology is a science that deals with cognitive and scientific frameworks in all areas of life, and it is one of the branches of philosophy that is concerned with the theory of knowledge, and it is also known as the science of science, and it is the mental act by which influence is carried out to the essence of the subject to understand a fact, and that most of the controversy and discussion in this branch revolves around the analysis of the nature of knowledge and its connections. With notations and terminology and the study of the means of knowledge production, and since it is considered a cognitive science that is concerned with critiquing knowledge with the aim of revealing its principles, conditions of origin and interpretations of reality and its products in terms of interest in concepts, methodological mechanisms and results in various sciences, it was found that it is possible to search and investigate through these knowledge In the world of communication, specifically network communication, since communication is a human practice and activities since ancient times, and it is still a common language of communication with others for understanding and exchanging ideas, information and opinions among themselves, which is the interaction that takes place between two independent parties (the sender and the receiver) and this response takes place in an environment and a social medium. . It is the process by which information, ideas and directions are transferred through a social system, culture, influences, social and environmental repercussions, subjective psychology, and objective processes of production and reflection according to the knowledge embedded in the design work so that it becomes part of the culture of the applicable thing.. This is what can be applied in the world of fashion by preparing plans A systematic strategy with epistemological knowledge frameworks between fashion designers and recipients (consumers) through social systems according to different and distinct societal implications in terms of ideas, motives, tendencies, desires, beliefs, class classification, economic, political, religious and effective deliberative conditions among these societal groups with their different genders and multiple affiliations...etc.All of this is centered in the field of knowledge of the sciences of network communication and its components and mechanisms, which lie in its effective effectiveness and affected by the societal repercussions that are raised through promotional advertisements, which are among the means of network communication, and it is generally one of the means of fashion design. One of the mechanisms of societal communication and communication languages ​​and one of the most attractive elements with its expressive values ​​through which the content controls the communication effectiveness to achieve marketing interaction between designers and clothing manufacturers and showrooms for fashion designs in different fashions in order to increase the response of the recipient and the consumer for the purpose of increasing sales and achieving the highest characteristics of commercial dealing and economic and and encourage competition between designers, producers and industrialists to provide their best to achieve cultural communication and technical development. This will be monitored by:1: The concept of epistemology and communication sciences.2: The culture of knowledge and societal repercussions.3: The world of fashion and fashion design and networking mechanisms.All of this can be obtained by exchanging knowledge experiences, societal behaviors, and the repercussions of endless development across the countries of the Arab world and the world at large, in order to increase the speed of permeability of ideas, knowledge sciences and developments to promote the product through network communication, which has become one of the most important areas of communication, which penetrated our current reality and became an outlet for marketing many products that Societies require it, including fashion, with its renewable and produced fashions in the countries of the Arab world or the whole world.